CHANGES MOTOR-RESEARCH ANIMAL BEHAVIOR UNDER THE INFLUENCE OF ANTIDEPRESSANTS UNDER THE EXPERIMENTAL EQUIVALENT OF MULTIPLE SCLEROSIS - Нефьодов, О.О. (World of Medicine and Biology, 2015)
Multiple sclerosis is the most common demyelinating disease that affects mainly young people of working age (16-45 years) and quickly leads to disability. Cognitive and emotional-affective disorders, most patients appear slowdown and the uniformity of the most important mental functions (attention, memory) and emotional background. It is shown that the introduction of additional trytikko and paroxetine increases motor activity indicators compared with those 12 days of the experiment, but remained lower than in the original condition. In addition, these treatment groups was observed positive dynamics research activity. It is shown that under conditions of administration of fluoxetine emotional animal improved: the number of acts and grooming bolus increased almost 2 times (compared with those initial state), the animals were calm anxiety was observed. Also the conditions EERS in animals with simulated pathology recorded changes in muscle tone in the initial state, and the 12 and 17 day formation process of demyelination. It has up to 12 days demyelination formation decreased muscle tone average of 1.5 - 2.5 times for all investigated groups. It is shown that more pronounced dynamics to strengthen muscle tone was registered against the backdrop of the introduction of fluoxetine and paroxetine. So investigated antidepressants (fluoxetine and trytikko) are promising for use as an adjuvant in the presence of pain is compatible with depressive disorders in patients with MS.
Keywords: research-oriented behavior; multiple sclerosis; antidepressants